2007
DOI: 10.1521/suli.2007.37.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Maintained Attitudinal Changes in Nursing Personnel After a Brief Training on Suicide Prevention

Abstract: Nursing personnel (N = 317) working at a general hospital attended a 6-hour training program on suicide prevention. They answered anonymously pre- and post-training the Suicide Behavior Attitude Questionnaire (SBAQ), which comprises 21 visual analogue scale items divided in three factorial subscales. The results indicated there were positive changes in the attitudes and these gains were significantly maintained at the 6-month follow-up evaluation. Improvement was in the Feelings and Professional Capacity subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 23 publications
5
68
0
7
Order By: Relevance
“…Sometimes it can be sufficient to devote more time to the elderly patient and encourage her/him to talk about the emotional pain and suffering. However, research has revealed negative attitudes towards suicide among nurses [50]. The belief that a person does not have the right to commit suicide was stronger among older nurses, those who had never taken care of suicidal patients, had a family history of suicide, who were Protestants and attended church services more frequently.…”
Section: A L Holm Et Al Open Journal Of Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes it can be sufficient to devote more time to the elderly patient and encourage her/him to talk about the emotional pain and suffering. However, research has revealed negative attitudes towards suicide among nurses [50]. The belief that a person does not have the right to commit suicide was stronger among older nurses, those who had never taken care of suicidal patients, had a family history of suicide, who were Protestants and attended church services more frequently.…”
Section: A L Holm Et Al Open Journal Of Nursingmentioning
confidence: 99%
“…The belief that a person does not have the right to commit suicide was stronger among older nurses, those who had never taken care of suicidal patients, had a family history of suicide, who were Protestants and attended church services more frequently. Greater professional capacity was reported by nursing assistants and nurses who had already taken care of suicidal patients [50]. Such negative attitudes can be sensed by the older patients, causing them to conceal their serious suicidal plans.…”
Section: A L Holm Et Al Open Journal Of Nursingmentioning
confidence: 99%
“…• Education and training of individuals: providing mental health education for employees [11][12][13][14] • Development of a support network: Development a support network among employees 14) , encouraging cooperation between managers and industry health staff 14) • Cooperation from internal and external resources:…”
Section: Workplacementioning
confidence: 99%
“…providing mental health education for managers or occupational health staff [11][12][13][14] The characteristic contents of suicide prevention programs at the workplace aimed to improve personnel management and health care 16) .…”
Section: Workplacementioning
confidence: 99%
See 1 more Smart Citation